1978
DOI: 10.1051/rnd:19780113
|View full text |Cite
|
Sign up to set email alerts
|

Etude ultrastructurale, chez un poisson téléostéen l'anguille (Anguilla anguilla L.), des processus de minéralisation dans les cas d'une ossification périchondrale de l'arc branchial et d'une apposition secondaire dans l'os vertébral

Abstract: Summary. Ultrastructural

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

1979
1979
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 7 publications
2
8
1
Order By: Relevance
“…Electron probe microanalysis and electron diffraction are now being used to determine the maturation sequence of the mineral phase with respect to some of the facets of its location within the demirays. From the present work, no apparent association exists between the mineral phase and extracellular vesicles found in distal fin bud regions, a result different from that described during calcification of epiphyseal growth plate cartilage in many species (Anderson, 1976;Anderson et al, 1970;Bonucci and Dearden, 1976) and during primary membranous ossification of the gill arch in the eel (Lopez et al, 1978). Indeed, in addition to the absence of dense needles or rods within vesicles as reported in epiphyseal cartilage and the gill arch, those extracellular vesicles that are observed in the fin bud of S. gairdneri are also dissimilar in size, shape, and electron density to the cellular projections found in rat predentin (Bernard, 1972) and to the membrane-bound extracellular structures reported during tooth development of the killifish (Yamada and Ozawa, 1978).…”
Section: Bone Formationcontrasting
confidence: 68%
“…Electron probe microanalysis and electron diffraction are now being used to determine the maturation sequence of the mineral phase with respect to some of the facets of its location within the demirays. From the present work, no apparent association exists between the mineral phase and extracellular vesicles found in distal fin bud regions, a result different from that described during calcification of epiphyseal growth plate cartilage in many species (Anderson, 1976;Anderson et al, 1970;Bonucci and Dearden, 1976) and during primary membranous ossification of the gill arch in the eel (Lopez et al, 1978). Indeed, in addition to the absence of dense needles or rods within vesicles as reported in epiphyseal cartilage and the gill arch, those extracellular vesicles that are observed in the fin bud of S. gairdneri are also dissimilar in size, shape, and electron density to the cellular projections found in rat predentin (Bernard, 1972) and to the membrane-bound extracellular structures reported during tooth development of the killifish (Yamada and Ozawa, 1978).…”
Section: Bone Formationcontrasting
confidence: 68%
“…5). Lopez et al [19] also reported similar findings in the eel, Anguilla anguilla, during perichondral ossification of the gill arch and secondary accretion in the vertebral bone. These dense bodies are slightly smaller (430-810 .~) than the average matrix vesicles in mammalian bone.…”
Section: Osteogenesis Of Celhdar Attd Acelhtlar Fish Bonementioning
confidence: 53%
“…However, there are no studies which examine the ultrastructure of fish bone except the work by Lopez et al [19] on eels. Observation of the cellular bone of Carassius auratus indicates it to be similar in cell types and structure to normal mammalian bone.…”
Section: Osteogenesis Of Celhdar Attd Acelhtlar Fish Bonementioning
confidence: 99%
“…We have not been able to distinguish the two stages of osteoblasts described by Lopez et al (1978) during perichondral ossification of the branchial arches in the eel (AnguzEla anguilla). From the electron micrographs presented by Lopez et al (1978), it would appear that the mineralization front is very broad. This, along with the fact that the bone they describe is cellular (and their second type of osteoblasts already partially embedded in osteoid) can account for the differences between our observations and those of Lopez et al (1978).…”
Section: Formation Of Perichondral Bonementioning
confidence: 88%